Efficient, non-stochastic, Monte-Carlo-like-accurate method for the calculation of the temperature-dependent mobility in nanocrystal films. Issue 20 (15th May 2018) - Gómez-Campos, Francisco M.; Rodríguez-Bolívar, Salvador; Skibinsky-Gitlin, Erik S.; Califano, Marco
Abstract : We present a new framework that enables speed-ups of several orders of magnitude compared to conventional Monte Carlo approaches, while maintaining a similar accuracy. Abstract : We present a new non-stochastic framework for the calculation of the temperature dependence of the mobility in nanocrystal films, that enables speed-ups of several orders of magnitude compared to conventional Monte Carlo approaches, while maintaining a similar accuracy. Our model identifies a new contribution to the reduction of the mobility with increasing temperature in these systems (conventionally attributed to interactions with phonons), that alone is sufficient to explain the observed experimental trend up to room temperature. Comparison of our results with the theoretical predictions of the hopping model and the observed temperature dependence of recent field-effect mobility measurements in nanocrystal films, provides the means to discriminate between band-like and hopping transport and a definitive answer to whether the former has been achieved in quantum dot films.